DARI KYUUSHUU KE RAN’IN: KARAYUKI-SAN DAN PROSTITUSI JEPANG DI INDONESIA (1885-1920) - Sri Pangastoeti (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2009)
Karayuki-san is a term referring to Japanese women who worked as prostitutes abroad from the Meiji Period (1868-1912) to the World War II. This study investigates the various conditions that encourage Japanese women to be karayuki-san, to understand the kinds of exploitations that the karayuki-san experienced during their journey to Indonesia and worked as prostitutes in some cities in Indonesia. The main data sources for this research are some diplomatic records (confidential and disclosed) obtained from the Japanese Consulate in Singapore and Batavia from Meiji 28 (1895) to Taisho 4 (1915), Dutch Colonial Governments Regulations related to Japanese migrants, particularly those collected in the Missive Gouvernements Secretaris (Mgs), and dialog records between Yamazaki Tomoko and the ex-karayuki-san that were recorded in Sandakan Hachiban Shookan (Sandakan No.8 Brothel).